Effect of Sewage Water on the Growth and Development of Fodder Tree Plantations - Banyal, Rakesh; Bhardwaj, S. D. (Indian Forester, 2003)
This experiment was carried out to find out the effect of using sewage water for irrigation as compared with tap water and without any irrigation on fodder plants in nursery stage. The results indicate that the survival per cent of plants irrigated with sewage water was slightly more (94.29%) , than plant irrigated with water (91.43%) , but significantly higher than plants left without irrigation (80.57%). The growth parameters considered ( plant height , collar diameter number of branches per plant and leaf area) showed initial incremental gain in plant height and collar diameter in plants irrigated with sewage water , as compared with the other two treatments. The number of branches per plant and leaf area followed the same pattern. It is , therefore , concluded that sewage water could be used for better establishment of fodder species and their luxuriant growth later on.